1998
DOI: 10.1289/ehp.98106511
|View full text |Cite
|
Sign up to set email alerts
|

Liver cell models in in vitro toxicology.

Abstract: In vitro liver preparations are increasingly used for the study of hepatotoxicity of chemicals. In recent years their actual advantages and limitations have been better defined. The cell models, slices, and mainly primary hepatocyte cultures, appear to be the most powerful in vitro systems, as liver-specific functions and responsiveness to inducers are retained either for a few days or several weeks depending on culture conditions. Maintenance of phase and phase 11 xenobiotic metabolizing enzyme activities all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
128
1
3

Year Published

2000
2000
2015
2015

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 300 publications
(136 citation statements)
references
References 240 publications
(177 reference statements)
4
128
1
3
Order By: Relevance
“…promotes retention of hepatocyte viability and liver-specific functions that are otherwise rapidly lost in vitro (2). This robust ''coculture'' phenomenon, although poorly understood, has wide-ranging applications in both therapeutic and diagnostic applications of engineered liver tissue (14)(15)(16). Using both conventional techniques and micropatterning approaches, we and others have previously found that the degree of interaction between the two cell types (''heterotypic interaction'') modulated the amount of liver-specific function retained in vitro (2,17).…”
Section: Resultsmentioning
confidence: 99%
“…promotes retention of hepatocyte viability and liver-specific functions that are otherwise rapidly lost in vitro (2). This robust ''coculture'' phenomenon, although poorly understood, has wide-ranging applications in both therapeutic and diagnostic applications of engineered liver tissue (14)(15)(16). Using both conventional techniques and micropatterning approaches, we and others have previously found that the degree of interaction between the two cell types (''heterotypic interaction'') modulated the amount of liver-specific function retained in vitro (2,17).…”
Section: Resultsmentioning
confidence: 99%
“…However it is essential use hepatocytes to understand and model metabolic phenomena (Guillouzo, 2008). That is why many tissue engineering processes have been developed to provide better environments for hepatocytes maintenance and development (Gebhardt, 2003;De Bartolo and Bader, 2001;Franklin and Yost, 2000;Guillouzo, 1998;De Kanter et al, 2002). Such environments must reproduce, as closely as possible, the in vivo conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Since then, use of isolated hepatocytes has provided an ideal system for evaluating many aspects of hepatic metabolism, including biochemical and cellular processes involved in the activation of toxic chemicals and environmental pollutants (Berry et al 1991;Baksi and Frazier 1990;Guillouzo 1998;Kelly et al 1998;Moon et al 1965;Rogiers et al 1995).…”
Section: Introductionmentioning
confidence: 99%